2019
DOI: 10.1111/jvim.15617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combined testing to simultaneously diagnose pituitary pars intermedia dysfunction and insulin dysregulation in horses

Abstract: Background The thyrotropin‐releasing hormone (TRH) stimulation test and the 2‐step insulin sensitivity test are commonly used methods to diagnose, respectively, pituitary pars intermedia dysfunction (PPID) and insulin dysregulation (ID). Objectives To investigate the diagnostic value of combining the TRH stimulation test and the 2‐step insulin sensitivity test to diagnose PPID and ID simultaneously. Animals Twenty‐seven adult horses, 10 control horses without PPID or ID, 5 horses with PPID only, 5 horses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…For horses in groups 1 and 3 (without TRH stimulation), whole blood was collected into plastic blood collection tubes containing ethylenediaminetetraacetic acid (EDTA) after jugular venipuncture for measurement of endogenous plasma ACTH concentration. For horses in groups 2 and 4 (with TRH stimulation), whole blood was collected by jugular venipuncture 30 minutes after the IV injection of 1 mg of TRH (Sigma‐Aldrich Pty Ltd [subsidiary of Merck], North Ryde BC, New South Wales, Australia) 18 . Within 2 hours of blood sampling, samples were centrifuged at 1000 g at 4°C for 10 minutes and plasma was separated and placed into cryovials with no additives.…”
Section: Methodsmentioning
confidence: 99%
“…For horses in groups 1 and 3 (without TRH stimulation), whole blood was collected into plastic blood collection tubes containing ethylenediaminetetraacetic acid (EDTA) after jugular venipuncture for measurement of endogenous plasma ACTH concentration. For horses in groups 2 and 4 (with TRH stimulation), whole blood was collected by jugular venipuncture 30 minutes after the IV injection of 1 mg of TRH (Sigma‐Aldrich Pty Ltd [subsidiary of Merck], North Ryde BC, New South Wales, Australia) 18 . Within 2 hours of blood sampling, samples were centrifuged at 1000 g at 4°C for 10 minutes and plasma was separated and placed into cryovials with no additives.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14] To remove some of the effects of these variables and improve the detection of subclinical PPID cases, the provocative thyrotropin-releasing hormone (TRH) stimulation test has been developed and is extensively used both clinically and in research. [15][16][17] However, as with measurement of plasma baseline ACTH concentration, there is similar variability with season, age, stress, and diet with the TRH stimulation test. 18,19 Although other diagnostic tools have been explored, they have limitations and are rarely used, making determination of plasma ACTH concentration the mainstay for the diagnosis of PPID.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dynamic testing is more sensitive to detect small changes in pituitary activity or insulin secretion. Performing a thyrotropin-releasing hormone stimulation test, an oral glucose test or a two-step insulin sensitivity test could have improved our assessment of the endocrine status of the mares [ 40 , 41 , 42 , 43 ]. In addition, including mares with PPID, ID or both disorders would have allowed us to identify and validate any significant changes in hormone concentrations among healthy and metabolic mares.…”
Section: Discussionmentioning
confidence: 99%